The Maillard reaction of a shrimp by-product protein hydrolysate: chemical changes and inhibiting effects of reactive oxygen species in human HepG2 cells. Issue 6 (10th June 2015) - Zha, Fengchao; Wei, Binbin; Chen, Shengjun; Dong, Shiyuan; Zeng, Mingyong; Liu, Zunying
<x xml:space="preserve">Abstract</x> A shrimp by-product protein hydrolysate via the Maillard reaction could alleviate cellular damage, but result in higher HMF and loss of nutritional quality.